Microwave Radiation Associated with Lightning Initiation Events of Negative Cloud-to-Ground Flashes - Sabri M.H.M.; Alkahtani A.A.; Ahmad M.R.; Baharin S.A.S.; Lu G.; Kawasaki Z.; Cooray V. (MDPI, 2023)
Antennas; Clouds; Lightning; Microwave sensors; Cloud-to-ground flash; Electric field change; High-frequency radiation; Initial electric field change; Leadtime; Lightning initiation; Positive streamers; Radiation pulse; Short-length positive streamer; Very high frequency; Microwaves; cloud to ground lightning; electric field; lightning; microwave radiation; sensor